Life Tree Drawings as a Methodological Approach in Young Adults’ Life Stories during Cancer Remission - Saarelainen, Suvi-Maria (Narrative Works, 2015)
This paper introduces a methodological approach that was utilized when the textual material and life tree drawings of young adults with cancer were analyzed as an interwoven ensemble. In order to take the visuals seriously, the article focuses on visual narrative analysis in order to give a clear description of how the drawings were analyzed as narratives. New insights are gained when the analysis process is introduced step by step as a genuine combination of narrative textual and visual analysis. Finally, the drawings reveal new layers of experiences in a form of metaphors that reflect support, self, body, and time.